Development of e-journal-based participatory-reflective evaluation model in Physical Education learning - Resty Gustiawati; Fahrudin Fahrudin; Terbit Surya; Muhamad Farhan Amien (Sriwijaya Journal of Sport, 2024)
Physical Education teachers still face obstacles in conducting learning evaluations, especially on game materials that require process assessment, group performance, and student learning reflection. Assessments are often not carried out optimally due to time constraints and the unavailability of instruments capable of systematically documenting the learning process. This study aims to develop a reflective participatory evaluation model based on electronic learning journals as an alternative evaluation that supports student engagement and self-reflection. The study uses a Research and Development (R&D) approach with the R2D2 model through the stages of product determination, design, development, and testing. The sampling technique used was purposive sampling involving 27 participants (undergraduate and postgraduate students) who have experience in Physical Education learning. The instrument covers three story domains (attitudes, knowledge, and skills) and is validated using Pearson correlation and Cronbach's Alpha reliability. All items are declared valid (r-calculated > r-table = 0.32) with an average validity of 0.88 for the participatory instrument and 0.84 for the reflection instrument; The reliability was in the high category (α = 0.935; 0.793; 0.783). The novelty of this research lies in the integration of the participatory-reflective evaluation model with an electronic learning journal platform that allows real-time documentation of the learning process and increases student autonomy within the Merdeka Belajar framework. The developed product is considered feasible and effective in supporting the evaluation of Physical Education Learning. Further research is recommended to test the application of this model at different school levels, integrate it with automated data analysis, and compare it with other evaluation models to obtain a more comprehensive view of its effectiveness.